A database study of the safety and effectiveness of daily growth hormone in treating more than 80,000 children with growth disorders worldwide: a plain language summary of publication - Mohamad Maghnie; Michael B. Ranke; Mitchell E. Geffner; Elpis Vlachopapadopoulou; Lourdes Ibáñez; Martin Carlsson; Wayne Cutfield; Raoul Rooman; Roy Gomez; Michael P. Wajnrajch; Agnès Linglart; Renata Stawerska; et al. (Therapeutic Advances in Endocrinology and Metabolism)
Summary Researchers looked at data from the largest and longest-running database of children with growth disorders who were treated with daily injections of a brand of growth hormone called Genotropin . The researchers used these data to better understand the safety and effectiveness of daily growth hormone treatment. Researchers showed that daily growth hormone treatment: ○ Increased the children’s heights, measured after 1 year of treatment. This was seen for all of the growth disorders studied. ○ Increased growth in children of different ages, with higher growth seen in children who had begun treatment before they started puberty. ○ Allowed short children to reach an adult height within the normal range. This was true even for children who did not begin treatment until early adolescence. ○ Was safe. Only a very small percentage (3%) of children had any side effects related to growth hormone treatment, the most common of which was headaches. When children reach the end of puberty, their growth plates close and they are unable to grow any taller. Once this happens, growth hormone treatment cannot increase their growth further and treatment should be stopped. The purpose of this plain language summary is to help you to understand the findings from recent research. Somatropin is used to treat the conditions under study that are discussed in this summary. Approval varies by country; please check with your local healthcare provider for more details. The results of this study may differ from those of other studies. Health professionals should make treatment decisions based on all available evidence and not on the results of a single study.